Screening of Acetic Acid Bacteria from Pineapple Waste for Bacterial Cellulose Production using Sago Liquid Waste - Nur Arfa Yanti; Sitti Wirdhana Ahmad; Sri Ambardini; Nurhayani Haji Muhiddin; La Ode Iman Sulaiman (Biosaintifika: Journal of Biology & Biology Education, 2017)
Bacterial cellulose is a biopolymer produced by fermentation process with the help of bacteria. It has numerous applications in industrial sector with its characteristic as a biodegradable and nontoxic compound in nature. The potential application of BC is limited by its production costs, because BC is produced from expensive culture media. The use of cheap carbon and nutrient sources such as sago liquid waste is an interesting strategy to overcome this limitation. The objective of this study was to obtain the AAB strain that capable to produce bacterial cellulose from sago liquid waste. Isolation of AAB strains was conducted using CARR media and the screening of BC production was performed on Hestrin-Schramm (HS) media with glucose as a carbon source. The strains of AAB then were evaluated for their cellulose-producing capability using sago liquid waste as a substrate. Thirteen strains of AAB producing BC were isolated from pineapple waste (pineapple core and peel) and seven of them were capable to produce BC using sago liquid waste substrate. One of the AAB strains produced a relatively high BC, i.e. isolate LKN6. The result of morphological and biochemical test was proven that the bacteria was Acetobacter xylinum. The result of this study showed that A. xylinum LKN6 can produce a high yield of BC, therefore this strain is potentially useful for its utilization as a starter in bacterial cellulose production.